Cancer-related microangiopathic hemolytic anemia in patients with advanced gastric cancer: a retrospective single-center analysis - Berger, Anne Katrin; Allgäuer, Michael; Apostolidis, Leonidas; Schulze-Schleithoff, Anna; Merle, Uta; Jäger, Dirk; Haag, Georg Martin (World journal of gastrointestinal oncology, 2020)
Cancer-related microangiopathic hemolytic anemia in patients with advanced gastric cancer: A retrospective single-center analysis
Gesehen am 13.02.2022